Physiological and Proteomic Analyses of Different Ecotypes of Reed (Phragmites communis) in Adaption to Natural Drought and Salinity - Li, Huan; Lin, Wen-Fang; Shen, Zhi-Jun; Peng, Hao; Zhou, Jia-Jie; Zhu, Xue-Yi (Frontiers in Plant Science, 2021)
Drought and salinity are the two major abiotic stresses constraining the crop yield worldwide. Both of them trigger cellular dehydration and cause osmotic stress which leads to cytosolic and vacuolar volume reduction. However, whether plants share a similar tolerance mechanism in response to these two stresses under natural conditions has seldom been comparatively reported. There are three different ecotypes of reed within a 5 km2 region in the Badanjilin desert of Northwest China. Taking the typical swamp reed (SR) as a control, we performed a comparative study on the adaption mechanisms of the two terrestrial ecotypes: dune reed (DR) and heavy salt meadow reed (HSMR) by physiological and proteomic approaches coupled with bioinformatic analysis. The results showed that HSMR and DR have evolved C4-like photosynthetic and anatomical characteristics, such as the increased bundle sheath cells (BSCs) and chloroplasts in BSCs, higher density of veins, and lower density and aperture of stomata. In addition, the thylakoid membrane fluidity also plays an important role in their higher drought and salinity tolerance capability. The proteomic results further demonstrated that HSMR and DR facilitated the regulation of proteins associated with photosynthesis and energy metabolism, lipid metabolism, transcription and translation, and stress responses to well-adapt to the drought and salinity conditions. Overall, our results demonstrated that HSMR and DR shaped a similar adaption strategy from the structural and physiological levels to the molecular scale to ensure functionality in a harsh environment.